2005
DOI: 10.1007/s10658-004-1983-9
|View full text |Cite
|
Sign up to set email alerts
|

Infection of wheat spikes by Fusarium avenaceum and alterations of cell wall components in the infected tissue

Abstract: The infection process of Fusarium avenaceum on wheat spikes and the alteration of cell wall components in the infected host tissue were examined by means of electron microscopy and cytochemical labelling techniques following spray inoculation at growth stage (GS) 65 (mid-flowering). Macroconidia of the pathogen germinated with one to several germ-tubes 6-12 h after inoculation (hai) on host surfaces. The germ-tubes did not penetrate host tissues immediately, but extended and branched on the host surfaces. Hyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 35 publications
(35 reference statements)
2
32
0
2
Order By: Relevance
“…Outside of Australia, strains of this fungus causes head blight of wheat (Golinski et al 2002;Kang et al 2005) and frequently are recovered from the grain and field stubble of a number of cereals (Hall and Sutton 1998;Turkington et al 2002). Fusarium avenaceum has been isolated from winter cereals in south-eastern Australia .…”
Section: Fusarium Avenaceum (Fries) Saccardomentioning
confidence: 99%
“…Outside of Australia, strains of this fungus causes head blight of wheat (Golinski et al 2002;Kang et al 2005) and frequently are recovered from the grain and field stubble of a number of cereals (Hall and Sutton 1998;Turkington et al 2002). Fusarium avenaceum has been isolated from winter cereals in south-eastern Australia .…”
Section: Fusarium Avenaceum (Fries) Saccardomentioning
confidence: 99%
“…Among these species, F. graminearum is the main causal agent of FHB (McMullen et al, 1997;Lević, 2008). F. avenaceum is regarded as a saprotroph on cereals by some authors (Summerell et al, 2003), but several studies confirmed the pathogenicity of this species on wheat (Jenkinson and Parry, 1994;Kang et al, 2005). F. verticillioides is an important pathogen of maize, but it does not cause FHB (Leslie and Summerell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat heads are most susceptible to F. graminearum infection for a short time period from flowering to the soft dough stage of kernel development. More recently, we elucidated in detail the infection process and pathway of spread of F. culmorum, F. graminearum, F. avenaceum and M. nivale in wheat spikes by means of light microscopy and scanning and transmission electron microscopy, and found that these pathogens exhibited a similar behaviour regarding infection and colonization of wheat spikes (Kang and Buchenauer 2000a;Kang et al 2004Kang et al , 2005. Furthermore, using enzyme-gold and immuno-gold labelling techniques, it has been demonstrated that these pathogens produced cell wall degrading enzymes such as cellulases, xylanases and pectinases at early stages of infection in wheat spikes (Kang and Buchenauer 2000b;Wanyoike et al 2002;Kang et al 2004Kang et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we elucidated in detail the infection process and pathway of spread of F. culmorum, F. graminearum, F. avenaceum and M. nivale in wheat spikes by means of light microscopy and scanning and transmission electron microscopy, and found that these pathogens exhibited a similar behaviour regarding infection and colonization of wheat spikes (Kang and Buchenauer 2000a;Kang et al 2004Kang et al , 2005. Furthermore, using enzyme-gold and immuno-gold labelling techniques, it has been demonstrated that these pathogens produced cell wall degrading enzymes such as cellulases, xylanases and pectinases at early stages of infection in wheat spikes (Kang and Buchenauer 2000b;Wanyoike et al 2002;Kang et al 2004Kang et al , 2005. In addition, immunogold labelling studies revealed a close relationship between the accumulation of Fusarium toxins in infected wheat spikes and the pathogenic changes in the host cells, colonization of the pathogen in the host tissues and symptom appearance (Kang and Buchenauer 1999).…”
Section: Introductionmentioning
confidence: 99%